The transformation of the Ede worldview through changes in marriage practices in Buon Ma Thuot City, Dak Lak Province, Vietnam - Huan, Nguyen Dinh (Edelweiss Applied Science and Technology, 2025)
This study examines the transformation of the Ede worldview through changes in marriage practices in Buon Ma Thuot City, Dak Lak Province, Vietnam. The purpose of this research is to analyze how modernization, urbanization, and external cultural influences impact the traditional marriage system of the Ede, a matrilineal ethnic group. Using an interdisciplinary approach, the study applies historical-social and anthropological perspectives, employing qualitative and quantitative methods, including surveys, field observations, and secondary data analysis. The findings reveal a significant shift from traditional kinship-based marriages toward more individualistic, love-based unions. The role of extended families in marriage arrangements is declining, while economic factors and interethnic unions are becoming more influential. The study concludes that these transformations present both challenges to preserving traditional Ede values and opportunities for fostering cultural integration. Practical implications suggest that policies should balance modernization with the conservation of essential cultural traditions, ensuring sustainable development in ethnic minority communities.